Intratumoural immunotherapies in oncology. (March 2020) - Xu, Wen; Atkinson, Victoria G.; Menzies, Alexander M.
Abstract: Although immune checkpoint inhibitors have become the standard of care for many tumours, the majority of patients fail to achieve sustained benefit, often owing to the lack of a T-cell inflamed tumour microenvironment (TME). Directly injected intratumoural therapies present a potential strategy to induce T-cell inflammation and convert a 'cold' immune-inert TME into a 'hot' immune-inflamed TME. Various approaches including chemoablation, oncolytic viral therapy, cytokines and agents targeting innate immunity such as Toll-like receptor agonists and stimulator of interferon genes agonists are in clinical development. Thus far, melanoma has led the way in intratumoural drug development owing to its relative immunogenicity and propensity for cutaneous metastasis easily amenable to injections. However, intratumoural therapies are moving to other tumour types and advances in endoscopic and interventional radiological techniques are allowing these agents to be injected into visceral lesions. This review provides an overview of the current status of intratumoural therapies in oncology, as well as future directions regarding therapeutic niches and appropriate trial design for intratumoural agents. Highlights: Intratumoural immunotherapies can potentially convert a 'cold' tumour microenvironment into 'hot'. Melanoma has led the way in intratumoural drug development. However, these treatments are moving to other tumour types, with visceral injections feasible. We review mechanism of action, trial data and future directions for intratumoural therapies. Treatments reviewed include oncolytic viruses, cytokines, PV-10, Toll-like receptor and stimulator of interferon genes agonists.